2022
DOI: 10.3390/ma15041379
|View full text |Cite
|
Sign up to set email alerts
|

Dipicolinate Complexes of Oxovanadium(IV) and Dioxovanadium(V) with 2-Phenylpyridine and 4,4′-Dimethoxy-2,2′-bipyridyl as New Precatalysts for Olefin Oligomerization

Abstract: Polyolefins are used in everyday life, including in the production of many types of plastic. In addition, polyolefins account for over 50% of the polymers produced in the world. After conducting the oligomerization reactions of 2-propen-1-ol, 2-chloro-2-propen-1-ol, and norborene, polyolefins are obtained. In this report, two complexes of oxovanadium(IV) and dioxovanadium(V) with dipicolinate, 2-phenylyridine, and 4,4′-dimethoxy-2,2′-bipyridyl as precatalysts for 2-propen-1-ol, 2-chloro-2-propen-1-ol, and norb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The dipicolinate oxovanadium(IV) and dioxovanadium(V) complex compounds with 4,4′-dimethoxy-2,2′-bipyridyl and 2-phenylpyridine ( Figure 1 ) were synthesized in the same way as described in the publications: 31 for [VO(dipic)(dmbipy)] · 2 H 2 O and 32 for [VOO(dipic)](2-phepyH) · H 2 O.
Figure 1 Simplified structural formulas of ( 1 ) [VO(dipic)(dmbipy)] · 2 H 2 O and ( 2 ) [VOO(dipic)](2-phepyH) · H 2 O (2D above, 3D below).
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dipicolinate oxovanadium(IV) and dioxovanadium(V) complex compounds with 4,4′-dimethoxy-2,2′-bipyridyl and 2-phenylpyridine ( Figure 1 ) were synthesized in the same way as described in the publications: 31 for [VO(dipic)(dmbipy)] · 2 H 2 O and 32 for [VOO(dipic)](2-phepyH) · H 2 O.
Figure 1 Simplified structural formulas of ( 1 ) [VO(dipic)(dmbipy)] · 2 H 2 O and ( 2 ) [VOO(dipic)](2-phepyH) · H 2 O (2D above, 3D below).
…”
Section: Methodsmentioning
confidence: 99%
“…The results of elemental analysis of oxovanadium(IV) for [VO(dipic)(dmbipy)] · 2 H 2 O are 47.46% C, 3.69% H, and 8.77% N, where analysis calculations are the following: 47.10% C, 3.93% H, and 8.68% N. All the results concerning the analysis of the physicochemical properties of this complex are described in the literature. 31 However, the second compound complex, ie, [VOO(dipic)](2-phepyH) · H 2 O was synthesized as crystals and for this reason it was subjected to XRD analysis. The complete crystallographic characterization of the obtained dipicolinate complex of dioxovanadium(V) with 2-phenylpyridine has been described in the publication.…”
Section: Methodsmentioning
confidence: 99%
“…The polycarboxylate oxovanadium(IV) and dioxovanadium(V) complex compounds (Figure 1) were synthesized according to the procedures described in the literature: [22,23] for [24] for [VO(ida)(bipy)]•2 H 2 O (Com-pound 3), [25] [VO(dipic)(dmbipy)]•2 H 2 O (Compound 4). The complex compound [VOO(dipic)](2-phepyH)•H 2 O was synthesized in crystalline form and all data specifying the XRD analysis of this complex have been described in the publication [22].…”
Section: Synthesismentioning
confidence: 99%
“…The results showed that these complexes after activation by MMAO-12 have very high catalytic activity of more than 1000 kg/(mol V • h). [24,25,26] The synthesis of the transition metal complex with welldefined structural features (selection of the appropriate ligand that shape steric hinge and electron density) and its skillful integration with the appropriate activator is an attractive strategy that allows to obtain the effective catalytic system for a specific oligomerization or polymerization process. In view of this, herein we investigated the ethylene polymerization and polar monomers oligomerization in the presence of dipicolinate oxovanadium(IV) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group studied oxovanadium(IV) and dioxovanadium(V) complexes with polycarboxylate anions such as thiodiacetate, oxydiacetate, dipicolinate and ligands: 1,10‐phenanthroline, 2‐phenylpyridine, 4,4′‐dimethoxy‐2,2′‐dipyridyl and 2,2′‐bipyridine as precatalysts for 3‐buten‐2‐ol, 2‐propen‐1‐ol, 2‐chloro‐2‐propen‐1‐ol and 2,3‐dibromo‐2‐propen‐1‐ol oligomerizations. The results showed that these complexes after activation by MMAO‐12 have very high catalytic activity of more than 1000 kg/(mol V ⋅ h) [24,25,26] …”
Section: Introductionmentioning
confidence: 99%